Trajectory of pulmonary congestion by lung ultrasound in patients with acute myocardial infarction and association with cardiac structure and function. (3rd October 2022) - Platz, E; Claggett, B; Jering, K S; Kovacs, A; Cikes, M; Winzer, E B; Rad, A; Lefkowitz, M; Gong, J; Kober, L; McMurray, J J V; Solomon, S D; et al.
Abstract: Background: The PARADISE-MI trial examined the efficacy of sacubitril/valsartan in patients with acute myocardial infarction (AMI) complicated by reduced left ventricular ejection fraction (LVEF), pulmonary congestion or both. Little is known about the trajectory and echocardiographic correlates of pulmonary congestion in this population. Purpose: We sought to assess the trajectory of pulmonary congestion using lung ultrasound (LUS) and its association with cardiac structure and function in a subset of patients enrolled in PARADISE- MI. Methods: Participants underwent 8-zone LUS at baseline and 8 months. B-lines were quantified offline, blinded to treatment group, clinical findings, timepoint and outcomes by a core laboratory. Paired t-tests, chi-squared tests, and linear regression analyses were conducted. Results: Among 152 patients (median age 65 years, 32% women, 35% obese, mean LVEF 41%), any B-lines were detectable in 87%, the median sum of B-lines in 8 zones was 4 [IQR 2–8], and 67% had ≥3 B-lines indicative of congestion. Greater number of B-lines at baseline was associated with larger left atrial (LA) size, higher E/e' and E/A ratios, greater degree of mitral regurgitation, worse right ventricular (RV) systolic function, and higher tricuspid regurgitation velocity (P trend <0.05 for all) (Figure 1). Among 115 patients with 8-month LUS data, there was a significant decline in number of B-lines from baseline (mean ± SD: −1.6±7.3; p=0.018). Adjusted for baseline, B-lines at follow-up were on average 6 (95% CI: 3, 9) higher in a patient who experienced an intercurrent heart failure (HF) event than a non-HF patient (p=0.001). Among 75 patients with ≥3 B-lines at baseline, a decrease in B-lines to <3, indicating decongestion, occurred in 37% and was similar in the sacubitril/valsartan and ramipril groups (36% vs. 39%, p=0.83). Conclusions: In this post-AMI cohort, sonographic B-lines, indicating pulmonary congestion, were common at baseline and were significantly higher at follow-up in those who developed HF. Worse pulmonary congestion at baseline was associated with prognostically important echocardiographic markers of LV filling pressure, pulmonary pressure, and RV function. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Novartis